In Search of Educational Inclusion A Classroom Proposal from Cooperative Learning and IRCTs - García Pajares, Rodrigo (2019)
This paper aims to show the experiences arising from the development of a proposal for educational innovation in an urban center of the city of Segovia (Spain). The purpose of the proposal is to achieve an inclusive classroom model in which all students feel part of the learning process. To achieve this, we have decided to unite the pedagogical model of Cooperative Learning (CL) together with the work with Information, Relationship, and Communication Technologies (IRCT). The reason why both elements are combined is the inclusive potential that they arise separately, as well as the interest in this type of educational practices. In order to assess whether this classroom proposal accomplished the stated objectives, a case study was carried out to verify its veracity empirically. This was elaborated from a qualitative analysis based on observation techniques. All the information collected leads us to the disclosure of some interesting conclusions about this field.